PENDIDIKAN IPS BERBASIS KEARIFAN LOKAL DENGAN PENDEKATAN ETNOPEDAGOGY DITINJAU DARI PRESPEKTIF KURIKULUM - Misnah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
The personal social issues experienced by students in daily life are important studies in social studies education. The study of the role of the environment is very important in preserving local wisdom that is beginning to be abandoned by the younger generation, especially the students as a generation of gold who will continue the eastafet stick of development. The importance of a learning approach that is relevant to the situation of students, learning in accordance with the real world reality of students with ecological intelligence (Ekopedagogy) by exploring local wisdom that can be developed through social studies with the selection of contextual material, and meaningful for students to develop skills concern for the community, and place empathy as a form of positive attitudes towards environmental conservation based on local wisdom through the ecopedagogy approach. Keywords: social studies, local wisdom, ethnopedagogy